Penentuan Faktor Teknis dan Politis Kunci Implementasi TOD di Surabaya Melalui Konsensus Pakar Berbasis Delphi - Anastasya Sabrina Rahmawati; Siti Nurlaela; I Dewa Made Frendika Septanaya (Jurnal Penataan Ruang, 2025)
Transit-Oriented Development (TOD) planning in Surabaya requires a comprehensive understanding of the strategic factors that influence its successful implementation. This study aims to identify both technical and political factors that must be considered in TOD implementation. This study applies a Delphi method involving six stakeholders from government, academia, and NGOs to identify strategic variables influencing TOD. Technical variables are assessed using 7D principles (Density, Diversity, Design, Destination Accessibility, Distance to Transit, Demand Management, and Demography) aligned with national regulations (Ministry of Agrarian Affairs and Spatial Planning Regulation No. 16/2017), while political factors cover institutional governance, regulations, and financing. Of the 43 sub-variables evaluated, most reached unanimous (full) consensus and two attained majority consensus. The findings highlight that TOD success in Surabaya depends not only on technical compliance but also on institutional coordination and policy responsiveness to local context.